Understanding low wage growth in the euro area and European countries - Christiane Nickel; Elena Bobeica; Gerrit Koester; Eliza Magdalena Lis; Mario Porqueddu (European Central Bank (ECB), 2019)
Despite notable improvements in the labour market since 2013, wage growth in the euro area was subdued and substantially overpredicted in 2013-17. This paper summarises the findings of an ESCB expert group on the reasons for low wage growth and provides comparable analyses on wage developments in the euro area as a whole and in individual EU countries. The paper finds that cyclical drivers, as captured by a standard Phillips curve, seem to explain much of the weakness in wage growth during this period, but not all of it. Going beyond the drivers included in standard Phillips curves, other factors are also found to have played a role, such as compositional effects, the possible non-linear reaction of wage growth to cyclical improvements, and structural and institutional factors. In order to increase the robustness of wage forecasts, the paper also proposes ready-to-use tools for cross-checking euro area wage growth forecasts based on wage Phillips curves. These are derived based on a comprehensive real-time forecast evaluation exercise
Keywords: J30; E24; E31; E32; 330; Wages; business cycles; structural factors; forecasting